A Rare Cause of Shoulder Pain: Osteosarcoma of the Scapula - Kadir Güler; Ayşe Dicle Turhanoğlu (Galenos Yayinevi, 2021)
Osteosarcoma is a malignant bone tumor usually seen in adolescent and early adulthood and often with long bones; patients complain of pain and swelling. Plain radiography revealed cortex destruction and moth-eaten style medullary lesions. Reported herein is a 31-year-old male patient with a history of scapular osteosarcoma who presented with a shoulder pain complaint. The importance of imaging, examination, and anamnesis is emphasized in the light of the literature.